Bishop Charles Davis's musical contribution to the early Australian Catholic Church - Pender, Graeme (The Australasian Catholic record, 2019)
This article will explore the musicianship of Bishop Charles Henry Davis, osb (1815-1854), coadjutor to Australia's first Catholic Archbishop, John Bede Polding, osb. It will focus on his musical contribution to the early Australian Catholic Church-his ability to improvise, compose, conduct and perform during his short time as bishop at St Mary's, Sydney (1848-54).